Myectomy for Giant Zenker’s Diverticulum - Abayli, Bahri; Simsek, Yeliz; Ozer, Ali Ilker; Kuvvetli, Adnan; Avci, Begum Seyda; Avci, Akkan (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Abayli B, Simsek Y, Ozer AI, Kuvvetli A, Avci BS, Avci A. Myectomy for giant Zenker’s diverticulum. Turk J Gastroenterol. Published online November 21, 2025. doi:10.5152/tjg.2025.25503.